2009
DOI: 10.1097/shk.0b013e3181a2b886
|View full text |Cite
|
Sign up to set email alerts
|

Edaravone, a Novel Free Radical Scavenger, Reduces High-Mobility Group Box 1 and Prolongs Survival in a Neonatal Sepsis Model

Abstract: Free radicals play an important role in the inflammatory process of sepsis. We hypothesized that edaravone, a novel free radical scavenger, can suppress pathophysiological events and prolong survival in a neonatal sepsis cecal ligation and perforation (CLP) model. Of 32 3-day-old anesthetized and mechanically ventilated piglets, 11 received CLP only, 10 received CLP and edaravone treatment starting 30 min after CLP, and 11 constituted a sham (control) group. Mean arterial pressure (MAP), heart rate, cardiac ou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
21
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 32 publications
(22 citation statements)
references
References 36 publications
1
21
0
Order By: Relevance
“…The O 2 scavenger edaravone has a suppressive effect on the release of cytokines and oxidative mediators and therefore can limit the oxidant-antioxidant imbalance associated with severe systemic inflammation and multiple organ damage in neonatal sepsis (25). This experiment demonstrated that ETR-P1/fl could similarly prevent the sepsis-induced elevation of oxidative stress mechanisms and thus improve the health of the cardiopulmonary system in neonatal sepsis.…”
Section: Discussionmentioning
confidence: 60%
“…The O 2 scavenger edaravone has a suppressive effect on the release of cytokines and oxidative mediators and therefore can limit the oxidant-antioxidant imbalance associated with severe systemic inflammation and multiple organ damage in neonatal sepsis (25). This experiment demonstrated that ETR-P1/fl could similarly prevent the sepsis-induced elevation of oxidative stress mechanisms and thus improve the health of the cardiopulmonary system in neonatal sepsis.…”
Section: Discussionmentioning
confidence: 60%
“…In recent years, some of the postulated molecular mechanisms of sepsis progression are related to the imbalance between ROS production and scavenging by the cellular anti-oxidant system [5,[34][35][36]. Lots of studies have shown that excessive production of ROS and other free radicals in sepsis, such as H 2 O 2 , superoxides and NO, which are associated with inflammation, lead to a condition of oxidative stress and contribute to high mortality rates [6,25].…”
Section: Discussionmentioning
confidence: 99%
“…H 2 O 2 actives the MAPK and NF-κB pathways, which in turn promotes HMGB1 release in macrophages and monocytes (Tang et al, 2007e). Antioxidants such as NAC (Tsung et al, 2007a), quercetin (Tang et al, 2009), edaravone (Kato et al, 2009), pyrrolidine dithiocarbamate (Zhang et al, 2010), and resveratrol (Delucchi et al, 2012) significantly inhibit HMGB1 release in several animal infection and injury models.…”
Section: Hmgb1 Releasementioning
confidence: 99%